UPAYA PENINGKATAN KUALITAS KOMPETENSI PROFESIONALISME GURU BAGI PESERTA DIDIK - Puspita Puji Rahayu; Menik Tetha Agustina; Qurnia Fitriyatinur (Jurnal Ilmiah Hospitality, 2022)
This form of community service activity aims to provide information or knowledge for educators in carrying out the teaching and learning process in schools. Activities are carried out through online seminars, which are aimed at the teaching profession for kindergarten, elementary, junior high, high school and university circles. The material presented covered three topics, including Pedagogic Competence for Educators in the Digital Age, Design of Fun Learning Methods to Increase Learning Motivation, and the Role of Educators as Role Models for Students in Character Development. After participants take part in an online seminar related to the above themes, it is hoped that educators can carry out their duties optimally in educating the nation's children by prioritizing the term "Teacher (at Gugu lan di Tiru)" in the sense that an educator can be used as an example and as a role model in implementing learning process